CORRUPTION AND POVERTY ALLEVIATION IN INDONESIA - Fitri Zahrotul Jannah; Dwi Susilowati (Jurnal Ilmu Ekonomi JIE, 2019)
Poverty is an economic problem that occurs in both developing and developed countries that have not been overcome. Percentage of poverty in Indonesia 10.12%. While the average provincial poverty rate in Indonesia is more than 50%. Therefore it is necessary to find a solution to overcome or at least reduce poverty. A growing economy is expected to reduce poverty. The requirement for sustainable economic growth is the existence of a fair system of government. This study aims to determine the effect of economic growth, the human development index, and corruption on poverty in the province of Indonesia. This research used secondary data from 2013 to 2017. The method used is panel data analysis method. The results show that the effect of economic growth on poverty is negatively insignificant, while for the variable corruption against poverty is a significant positive and for the human development index on poverty is a significant negative.